2018
DOI: 10.1111/geb.12760
|View full text |Cite
|
Sign up to set email alerts
|

Nativity and seed dispersal mode influence species’ responses to habitat connectivity and urban environments

Abstract: Aim: Urbanization alters local environmental conditions and the ability of species to disperse between remnant habitat patches within the urban matrix. Nonetheless, despite the ongoing growth of urban areas worldwide, few studies have investigated the relative importance of dispersal and local environmental conditions for influencing species composition within urban and suburban landscapes. Here, we explore this question using spatial patterns of plant species composition. Location: The Research Triangle area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…); indeed, in a related study (Lopez et al. ), we found a time lag between reductions in habitat connectivity due to urban development and corresponding changes in species composition. Habitat transformation is also more likely to have overall negative effects on biodiversity in habitat types that are systematically replaced or transformed by urban development, such as some types of wetlands (Williams et al.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…); indeed, in a related study (Lopez et al. ), we found a time lag between reductions in habitat connectivity due to urban development and corresponding changes in species composition. Habitat transformation is also more likely to have overall negative effects on biodiversity in habitat types that are systematically replaced or transformed by urban development, such as some types of wetlands (Williams et al.…”
Section: Discussionsupporting
confidence: 70%
“…Despite the direct negative effect of habitat transformation on native and overall species richness, we found that the total effects of habitat transformation, including its indirect effects via environmental variables and fragmentation, were positive. These positive effects may be short-term changes that could reverse with the onset of extinction debts in the future (Hahs et al 2009); indeed, in a related study (Lopez et al 2018), we found a time lag between reductions in habitat connectivity due to urban development and corresponding changes in species composition. Habitat transformation is also more likely to have overall negative effects on biodiversity in habitat types that are systematically replaced or transformed by urban development, such as some types of wetlands (Williams et al 2009), than in the relatively intact riparian forests we studied.…”
Section: Direct and Indirect Effects Of Habitat Transformationsupporting
confidence: 58%
See 2 more Smart Citations
“…Insights gained from urban forest patches at the landscape scale (Wu 2014) have contributed to an increased understanding of plant functional groups and forest edges in cities (Godefroid and Koedam 2003a) and biodiversity conservation (Sukopp and Weiler 1988;Löfvenhaft et al 2002;Godefroid and Koedam 2003b). Others have examined patterns of change in forest patch size, shape, and number (Zipperer et al 2012), and have emphasized the importance of the urban landscape matrix to native and non-native species dispersal (Lopez et al 2018). Recent city or metropolitan region-wide approaches have yielded new insights such as indicating that land cover, land use histories, and pre-urban vegetation have lasting effects on ecosystem structure and function (e.g., Fahey et al 2012;Carter et al 2015;Fahey and Casali 2017).…”
Section: Ecology In and Of Urban Forest Patchesmentioning
confidence: 99%